FactoryIoTSim: towards a real-time IoT events simulator - Yang, Yubei (Nanyang Technological University, 2022)
The adoption of the Internet of Things (IoT) has dramatically impacted the manufacturing industry, changing its traditional supply chains into an interconnected and dynamic system. In a semiconductor manufacturing factory, a product is processed at multiple machines. However, these machines may stop working due to scheduled maintenance or unexpected breakdowns, affecting the production schedule. IoT can be deployed in the factory to detect the production status and monitor for breakdowns. However, the deployment of IoT in a real-world factory for research and development will be a costly endeavor. This project shows how IoT is simulated in a wafer-fab factory for the correct implementation and development of IoT applications without costly investment in IoT systems and networks. To simulate the production process, we develop a semiconductor manufacturing factory simulator to simulate the factory process and its sensors. A simulation is implemented based on a real-world factory scenario, and the sensor output from the simulation is used to generate real-time events to be sent to an IoT Hub. To showcase the simulator, an IoT application is designed to monitor the events at the IoT Hub to detect machine breakdowns.